2021
DOI: 10.1186/s40035-021-00254-1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of physical exercise in neurodegeneration: reversal of epigenetic clock

Abstract: The epigenetic clock is defined by the DNA methylation (DNAm) level and has been extensively applied to distinguish biological age from chronological age. Aging-related neurodegeneration is associated with epigenetic alteration, which determines the status of diseases. In recent years, extensive research has shown that physical exercise (PE) can affect the DNAm level, implying a reversal of the epigenetic clock in neurodegeneration. PE also regulates brain plasticity, neuroinflammation, and molecular signaling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 171 publications
(192 reference statements)
0
24
0
1
Order By: Relevance
“…Recently, many studies have reported the beneficial effects of physical activity in a number of neurodegenerative diseases, underlining the neuroprotective effect of exercise [48][49][50][51]. Physical activity can indeed increase the expression of the genes involved in antioxidant defense, can counteract the debilitating effects of many pathologies of the nervous system, and can even improve cognitive functions and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies have reported the beneficial effects of physical activity in a number of neurodegenerative diseases, underlining the neuroprotective effect of exercise [48][49][50][51]. Physical activity can indeed increase the expression of the genes involved in antioxidant defense, can counteract the debilitating effects of many pathologies of the nervous system, and can even improve cognitive functions and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our data suggest that one mechanism for the observed therapeutic effects of exercise on brain cognitive health may be improvements in circulating plasma cytokines. It might also be of interest in the future to measure the effects of physical exercise on biological aging using an DNA methylation epigenetic clock in parallel with the EEG based BAI [70]. The findings of our current study warrant future research to further characterize the mechanisms by which exercise improves cognitive functions.…”
Section: Discussionmentioning
confidence: 83%
“…In human and animal models, the multiple benefits of regular physical exercise have been fully demonstrated. Whether aerobic exercise, anaerobic exercise or resistance exercise, are all considered to be beneficial to physical and mental health ( Xu et al, 2021 ). More and more evidence showed that physical exercise can help maintain optimal cerebrovascular function, thereby preventing or slowing down the occurrence and development of cognitive impairment ( Bliss et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%